Repeated Exposure to Streptococcus pneumoniae Exacerbates Chronic Obstructive Pulmonary Disease - Gou, Xuxu (Am J Pathol, 2019)
Streptococcus pneumoniae is commonly found in patients with chronic obstructive pulmonary disease (COPD) and is linked to acute exacerbation of COPD. However, current clinical therapy neglects asymptomatic insidious S. pneumoniae colonization. We studied the roles of repeated exposure to S. pneumoniae in COPD progression using a mouse model. C57BL/6J mice were intranasally inoculated with S. pneumoniae ST262 every 4 weeks with or without cigarette smoke (CS) exposure up to 20 weeks to maintain persistent S. pneumoniae presence in the lower airways. Streptococcus pneumoniae enhanced CS-induced inflammatory cell infiltration at 12 to 20 weeks of exposure. Streptococcus pneumoniae also increased CS-induced release of inflammatory cytokines, including IL-1β, tumor necrosis factor-α, IL-12 (p70), and IL-5 at 20 weeks of exposure. Moreover, a combination of CS and S. pneumoniae caused alveolar epithelial injury, a decline in lung function, and an increased expression of platelet-activating factor receptor and bacterial load. Our results suggest that repeated exposure to S. pneumoniae in lower airways exacerbates CS-induced COPD.